Complementary Feeding Practice: A Phenomenological Approach - Janggu, Jayanthi Petronela; Hamat, Viviana (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Inappropriate complementary feeding practices remain a prevalent issue in developing countries. Mothers need to possess both adequate knowledge and proper implementation of complementary feeding (MP-ASI) to support optimal child growth and development and to prevent disease and nutrient absorption disorders caused by inadequate complementary feeding. This study aims to explore mothers’ experiences in practicing complementary feeding. A qualitative research design using a descriptive phenomenological approach was employed to investigate the lived experiences of mothers regarding complementary feeding practices. The study identified three major themes: (1) maternal knowledge about complementary feeding, (2) emotional experiences during the practice of complementary feeding, and (3) mothers’ perceptions of the causes influencing complementary feeding practices. The findings suggest that maternal knowledge regarding complementary feeding remains relatively limited. Furthermore, mothers often experience feelings of worry, confusion, and stress while feeding their children, particularly when children refuse certain foods. These emotional responses are considered normal under such circumstances and are influenced by both direct and indirect factors affecting complementary feeding.